The Politics of Collaborative Governance in Local Health Promotion in the Philippines: Determinants, Risks, and Institutional Reforms - Reiou Regie Manuel; Rizalino B. Cruz (Indonesian Association for Public Administration, 2026)
Public health promotion at the local level is a critical yet often overlooked aspect of health governance in the Philippines. While health promotion initiatives have been studied, there is limited empirical analysis on how local governance structures, political dynamics, and institutional coordination shape health promotion implementation at the local level. Giv- en the decentralized nature of health governance in the country, frontline health workers, local officials, formal and informal institutions play a pivotal role in health promotion. Yet, their actions are often constrained by transaction costs and political disincentives. Building on the Institutional Collective Action (ICA) framework and the Political Market Framework, this paper tackles the factors shaping collaborative governance in health pro- motion by local government units (LGUs). Specifically, it raises the questions: What are the factors impeding collaboration among health promotion stakeholders at the local lev- el? How do coordination, division, and defection risks shape day-to-day implementation? What formal and informal reforms have been adopted to mitigate those risks? A qualitative study is employed using Malabon City as a case study. Key informant inter- views, focus group discussions, and policy document review provide qualitative insight into the governance dynamics across 21 barangays constituting the smallest administra- tive units in the Philippine governance system. Findings reveal that: (i) ambiguous mandates and overlapping roles inflate negotiation, monitoring, and enforcement costs; (ii) partisan gatekeeping turns health promotion ben- efits into club goods, producing spatially and politically uneven service access; and (iii) informal networks and social capital of Barangay Health Workers (BHW) partially substi- tute for formal mechanisms but remain vulnerable to electoral turnover. Where transac- tion costs are minimized – e.g., through ordinances institutionalizing Health Promotion Units, pooled budgeting for multi-barangay health centers, and merit-based BHW tenure – collaboration gains stability and scale.